Analysis of Level Team Effectiveness in The Implementation of Scrum Using Evidence-Based Management (Case Study: Company A as A Fintech Industry) - Putri, Riski Puspa Diangga; Fatichah, Chastine (IPTEK, DRPM, Institut Teknologi Sepuluh Nopember, 2023)
In implementing Scrum in Company A, which is a fintech company, there is a Scrum Master who is responsible for ensuring the effectiveness of the Scrum team. The Scrum Master of Company A still uses the velocity chart to measure team effectiveness. Still, the use of the velocity chart itself cannot describe the level of responsiveness of the team in delivering products to users. In this study, the applica- tion of EBM is used as a metric to replace the velocity chart in analyzing the level of effectiveness of the Scrum team in Company A. Through FGDs with senior Scrum Masters. The EBM metric was selected to be used in the analysis. The application of EBM is carried out by collecting primary data from each team and secondary data from company data. Data from each team was analyzed and weighted. The results of this study indicate the effectiveness score of each team. Based on these scores, the Scrum Master can determine which team’s process needs to be improved. This research can be used as an illustration for companies that implement Scrum in mea- suring the effectiveness of Scrum teams.